TEACHERS’ STRATEGY USED IN TEACHING READING COMPREHENSION IN THE CLASSROOM - Harpen Silitonga; Karolina Sinulingga; Nona Sony Manihuruk; Christian Neni Purba (Merwinspy Publisher, 2023)
Reading is one of the language skills which is very important to be learned by students. Through this activity, students can improve their own language and experience. The objectives of this research to find out the English teacher’s strategies in teaching reading comprehension and the advantages of using strategy. The research designed this study with qualitative method with the data from observation teaching learning process at SD HKBP Sidorame. The findings show that: the strategies commonly used by the English teacher in teaching reading comprehension at ten grade students of SMA HKBP Sidorame are question-answer relationship and discussion. The former eases the teacher in recognizing the students’ comprehension about the text, and helps the students develop an awareness of the multiple source of information in their reading. The later makes the students learn not only from the teacher but also from their fellow, and this strategy creates the active classroom atmosphere. In short, the mentioned strategies provide good contribution for both parties in the classroom: teacher and students.